Factors Related to Implementation Early Initiation of Breastfeeding (IMD) in Particular Women at PMB Bika Hardi, S.ST Padang - Eravianti, Eravianti; Pratiwi, Rahmi; Herayono, Febby; Darma, Ika Yulia; Yuliva, Yuliva (PT. Riset Press International, 2024)
IMD is giving newborn babies the opportunity to breastfeed themselves from the mother within the first hour of birth. IMD implementation in Indonesia has decreased from 58.2% in 2019 to 48.6% in 2021. West Sumatra also experienced a decline in 2020 by 29.64%, in 2021 by 25.84% and in 2022 by 25.68%. The aim of this research is to determine the factors related to the implementation of early initiation of breastfeeding (IMD) among mothers giving birth at PMB Rika Hardi, S.ST Padang in 2023. The type of research used is descriptive analytic using a cross sectional approach. This research was carried out from September 2023 to April 2024 at PMB Rika Hardi, S.ST Padang. The sampling technique used in accidental sampling. Data processing techniques using editing, coding, data entry, tabulating, cleaning and data analysis using univariate analysis and bivariate analysis using the Chi-Square test. The research results showed that 35.7% did not implement IMD, 33.3% had a low level of knowledge, 54.8%. family does not support, 42.9% of health workers do not support. There is a significant relationship between knowledge, family support, support from health workers and the implementation of IMD at PMB Rika Hardi, S.ST Padang in 2023. Knowledge factors, family support, health worker support are related to the implementation of IMD. It is hoped that the results of this research can be used in providing midwifery care for mothers giving birth, apart from that it canalso be a reference for midwives in providing intensive counseling to expectant mothers about the importance of exclusive breastfeeding starting from IMD so that the quality of service increases.